Transformasi digital perbankan syariah: Strategi peningkatan inklusi dan literasi keuangan di era digital - Siswanto, Seno Adji (Maliki Interdisciplinary Journal, 2025)
Digital transformation has fundamentally changed the landscape of Islamic banking in Indonesia. This research analyzes the role of digitalization in enhancing Islamic financial inclusion through the development of public digital literacy. Using a descriptive qualitative approach with literature study methods, this study examines various aspects of Islamic banking digital transformation including digital banking services, Islamic fintech, and strategies to increase financial service accessibility. The results show that digitalization has a significant positive impact on economic growth and Islamic financial inclusion, with digital banking transactions increasing by 27.6% and Indonesia’s digital economy value reaching Rp714.4 trillion. However, challenges such as low digital literacy, technology infrastructure gaps, and data security remain major obstacles. This research recommends the importance of synergy between government, Islamic financial institutions, and technology providers to develop an inclusive and sustainable Islamic fintech ecosystem.